Creating a CLT Environment for Improving Students’ Communicative Competence. (International conference on multidisciplinary science, 2025)
This research work focuses on the approaches to communicative language teaching and its significance in terms of language teaching and learning. The actual purpose of the paper is to explore the causes of failure of CLT in teaching in order to suggest the ways to make it successfully effective in the context and to analyze approaches to communicative language teaching.Many Eastern and Western scholars have studied this method. They are Rogova, Hoshimov, Zaripov, J. Jalolov, J. Rihards, S. Thornburry, H. Alyusf, D.Glenn, C.Harrison, A.Johnson, K. Lems, Admondson, Leather, Harmer, Philips.The main section outlines the advantages of comparing English language teaching with traditional methods of interactive and effective methods. It is well-established that the use of gambling techniques in organizing the lesson is effective. It enhances students' interest in the lesson, promotes their activity and teaches teamwork. There are techniques to improve the reading, writing, listening, listening skills used in English, and provide a game that enhances speech and critical thinking.